Mobility-based topology control of robot networks - Poduri, Sameera (ProQuest Dissertations & Theses, 2008)
A fundamental problem that arises in realizing large-scale wireless networks of mobile robots is that of controlling the communication topology. This thesis makes three contributions to the area of mobility-based topology control in robot networks. First, this work proposes local, geometric conditions on robot positions that guarantee global network connectivity. When combined with distributed controllers for mobile robots, these conditions maximize sensing coverage while maintaining connectivity. The key idea is the introduction of a new construct - a Neighbor-Every-Theta (NET) graph - in which each node has at least one neighbor in every angular sector of size . We prove that for < π, NET graphs are guaranteed to have an edge-connectivity of at least floor [special characters omitted], even with an irregular radio communication range. The NET conditions are integrated into an artificial potential field-based controller for distributed deployment. Second, for robots communicating over unreliable wireless links, a coalescence behavior is introduced, in which disconnected robots recover connectivity by searching for others. Our contribution is an asymptotic analysis of coalescence time which quantifies the trade-off between the cost of maintaining connectivity and that of repairing connectivity - the first such guideline for designing controllers for robot networks. Finally, having shown how to construct and maintain robot networks with maximal coverage, we address a problem motivated by the performance of cheap, low-resolution cameras in complex outdoor environments. This variation of the sensor coverage problem is the first to address the case where the sensing performance of each robot carrying a camera depends on the local environmental conditions. We present a distributed reconfiguration algorithm for this case, and validate it using a network of real Cyclops cameras placed in environments with varying illumination and backgrounds.